Proses Collaborative Governance Dalam Program Pengurangan Sampah Di TPA Jabon, Kabupaten Sidoarjo - Lutfia Diva Rahmawati; Ghulam Maulana Ilman (Universitas 17 Agustus 1945 Semarang, Indonesia, 2023)
The problem of waste is a complex problem that will never end, especially in developing countries. The increasing population of humans is accompanied by an increase in the amount of waste generated. Sidoarjo Regency is a regency that is registered as the regency with the largest volume of waste in East Java, which causes overload of waste in its landfill. This research aims to clearly understand the process of collaborative governance in the waste reduction program at Jabon Landfill, Sidoarjo. This research method uses a qualitative method. Data collection was carried out through documentation and literature study. The data analysis method in this study is descriptive-qualitative. The theory used in this study is the collaborative governance theory by Ratner (2012). The results of this study show that the collaborative governance process that occurs in the